AB1039 Diet may play essential role for the success of the urate lowering therapy in gout. (12th June 2018) - Kalkan, N.B.; Tezcan, M.E.
Abstract : Background: Chronic deposition of monosodium urate crystals, in case of hyperuricemia, is the main cause of the gout. 1 Furthermore, lowering uric acid to the targeted levels is the main therapeutic objective in chronic gout treatment. Uric acid lowering treatment (ULT) has three main arms: Practicing lifestyle modifications, pharmacologic ULT and targeting co-morbid illnesses. 2 Thus, patients' medical and therapeutic properties may have a role in successful ULT. Objectives: We evaluated the demographic and therapeutic properties; co-illnesses and disease features of the patients that would relate with the success of ULT. Then, we compared these parameters between the gout patients with successful ULT and inadequate ULT. Methods: 66 gout patients on pharmacologic ULT were enrolled to the study. Non-adherence to pharmacologic ULT was accepted an exclusion criteria. Demographic and therapeutic features; co-illnesses and disease features of the patients were obtained during the study. Then, we compared these parameters between the patients with successful ULT and inadequate ULT. Results: Adherence to diet was found different between groups (OR, 7.00; CL%95 2.27–21.56). All other features including maximum allopurinol dosage were similar. Only one patient from sucessful ULT group and none of the patients in inadequate group had an drinking habit. Conclusions: We found that diet was the only factor that relate with success of ULT while patients were on pharmacologic ULT. So, clinicians should emphasise the importance of all part of ULT including diet with informing patients about the nature of disease and benefits of ULT during visits. References: [1] Dalbeth N, Merriman TR, Stamp LK. Gout. Lancet2016; 388: 2039–52. [2] Khanna D, Fitzgerald JD, Khanna PP, Bae S, Singh MK, Neogi T, et al. 2012American College of Rheumatology guidelines for management of gout. Part 1: systematic nonpharmacologic and pharmacologic therapeutic approaches to hyperuricemia. Arthritis Care Res (Hoboken)2012; 64: 1431–46. Acknowledgements: None Disclosure of Interest: None declared